2019
DOI: 10.1155/2019/7395962
|View full text |Cite
|
Sign up to set email alerts
|

Albizia julibrissin Ameliorates Memory Loss Induced by Insomnia in Drosophila

Abstract: In clinical practice in Taiwan, Albizia julibrissin is the most prescribed Chinese herbal medicine for insomnia. Short-term insomnia and hypnotic use both attenuate cognitive functions, especially learning memory. In previous studies, A. julibrissin exhibits sedative activity, antidepressant-like effects, and protection of learning and memory against amnesia. However, whether A. julibrissin ameliorates memory loss caused by short-term sleep deprivation is not clear. We utilized the sleep-deprived Drosophila mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Si et al [ 61 ] found that BH could alleviate insomnia by modulating the composition, diversity, and metabolites of rats’ gut microbiota. Chang et al [ 62 ] reported that HHH could improve the memory loss induced by short-term sleep deprivation in fruit flies. Lee et al [ 63 ] found that KS and its bioactive compound, marine, promoted the transition from nonrapid eye movement sleep to rapid eye movement sleep by activating the VLPO neurons and modulating serotonin transmission in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Si et al [ 61 ] found that BH could alleviate insomnia by modulating the composition, diversity, and metabolites of rats’ gut microbiota. Chang et al [ 62 ] reported that HHH could improve the memory loss induced by short-term sleep deprivation in fruit flies. Lee et al [ 63 ] found that KS and its bioactive compound, marine, promoted the transition from nonrapid eye movement sleep to rapid eye movement sleep by activating the VLPO neurons and modulating serotonin transmission in rats.…”
Section: Discussionmentioning
confidence: 99%
“…46 Using the learning and memory of the sleep-deprived Drosophila model, the boiled water extracts (drugs : water = 6 kg : 6 L) of Albiziae Flos (4.5 and 18 mg/mL) have been proved to effectively ameliorate memory loss induced by sleep deprivation. 47 However, the mechanisms underlying the antidepressant effects of Albizia julibrissin remain as an ongoing challenge.…”
Section: Herbs For Depression Treatmentmentioning
confidence: 99%